2008
DOI: 10.1016/j.ecolecon.2007.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Multi-agent simulations to explore rules for rural credit in a highland farming community of Northern Thailand

Abstract: Multi-agent systems (MAS) open new modelling and analysis perspectives in ecological and social sciences. An original characteristic of the Companion Modelling (ComMod) approach adopted in this case study is the co-construction and use of a MAS model with and for local stakeholders such as farmers and local administrators. Alternating iteratively field and modelling activities, this approach facilitates collective learning among local stakeholders and between them and the researchers. Combining the use of MAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 22 publications
(25 reference statements)
0
18
0
3
Order By: Relevance
“…The question which must be addressed is how does the design of a model influence this perception? To avoid a "black box" effect, the model should be transparent and produce outputs that make sense to the farmer (Rivington et al, 2007;Barnaud et al, 2008). An understanding of the kind of learning derived through the use of the model, both for farmers and the researcher or advisor working with them, also is critical (Matthews et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The question which must be addressed is how does the design of a model influence this perception? To avoid a "black box" effect, the model should be transparent and produce outputs that make sense to the farmer (Rivington et al, 2007;Barnaud et al, 2008). An understanding of the kind of learning derived through the use of the model, both for farmers and the researcher or advisor working with them, also is critical (Matthews et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, various experimental simulation technologies, including multi-agent systems, system dynamics, and game theory have been applied to credit systems simulation to explore the creation and evolution mechanisms of credit. For example, Barnaud et al 2008 employed multiagent system models with role-playing games (RPG) to simulate rural credit in a highland farming community of Northern Thailand. The authors found that an informal credit system between friends reduced credit fraud.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The research approaches show that existing studies can be categorized according to two main schools of thought -traditional and emerging credit theories. While the former investigates credit theory based on various economics theories, e.g., institutional economics, information economics, and game theory (Stiglitz and Weiss 1981;Jarrow and Xu 2010;Brown and Zehnder 2010), the emerging studies utilize various current experimental techniques for complex systems, such as multi-agent-based models, system dynamics, and other simulation methods (Jankowitsch et al 2007;Barnaud et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most mountainous areas of nor ther n Thailand covered by lower montane forest (Bunavejchewin et al 2011), long history of shifting cultivation by local and hilltribe people has also caused gradual fragmentation of PFs (Buergin 2003, Barnaud et al 2008, Fukushima et al 2008) and increases forest edge especially, in protected area such as wildlife sanctuary and national park (Royal Forest Department 2010). Local people cultivated rice, maize, cabbages, and fruit crops after slash-and-burn clearing of forest areas, though some of them have been abandoned.…”
Section: Introductionmentioning
confidence: 99%